Indigenous perspectives on the biodigital convergence. (March 2022) - Williams, Keith; Brant, Suzanne
The biodigital convergence describes the intersection, and in some cases merging, of biological and digital technologies. Biodigital technologies include mRNA vaccines used to treat COVID-19, digitally controlled surveillance insects, microorganisms genetically engineered to produce medicinal compounds, and more. While significant scholarship has been paid to the ethical dimensions of biodigital technologies from a Western standpoint, little attention has focused on Indigenous views on the biodigital convergence. In this article, we explore the biodigital convergence from a Haudenosaunee perspective and suggest that insights from Indigenous philosophical traditions—specifically regarding relationality and territory—may be necessary for humanity to adapt to the profound and existential changes implicit in the biodigital convergence.